Tobacco control in China: the dilemma between economic development and health improvement Control del tabaco en China: el dilema entre desarrollo económico y salud - Hong Wang (Instituto Nacional de Salud Pública, 2006)
Although China's National People's Congress announced its decision to ratify the WHO's Framework Convention on Tobacco Control (FCTC) on Sunday, August 28, 2005, fundamental challenges to tobacco control still exist. A survey at the "No Smoking Day" on May 31, 2004 in China showed that over 73% of respondents do not think that human society will be able to get rid of the consumption of tobacco products. Although the prevalence of smoking declined 1.2% from 1996 to 2002, the absolute number of smokers increased by 30 million during this period. It is estimated that smoking prevalence will decline 10% in the next 25 years. However, due to the population increase, the total number of tobacco consumers will be about the same as today, which is 320 million. As long as the tobacco industry continues to be significant in overall economic development, and as long as the government continues to play a significant role in tobacco production, the debate between tobacco production and tobacco control will continue. Although China has already made significant efforts with regard to tobacco control, it is still in the beginning of its "long march" towards improving the population's health status by reducing tobacco consumption in China. A pesar de que el Congreso Nacional de la Población de China anunció su decisión de ratificar el Convenio Marco sobre Control de Tabaco (CMCT) el domingo 28 de agosto del 2005, los desafíos fundamentales a dicho control todavía existen. El análisis de "Un día sin tabaco", llevado a cabo el 31 de mayo del 2004 en China, demostró que alrededor de 73% de los encuestados no piensan que la sociedad esté dispuesta a liberarse del consumo de los productos de tabaco. Aunque el predominio de fumadores disminuyó en 1.2% de 1996 al 2002, su número total se incrementó a 30 millones durante este periodo. Se estima que la prevalencia de fumadores disminuirá en un 10% en los próximos 25 años. Sin embargo, debido al aumento de la población, el total de consumidores de tabaco será próximo al actual, esto es, cerca de 320 millones. Mientras que la industria tabacalera siga siendo significativa en el desarrollo económico y los gobiernos aún jueguen un papel específico en la producción del tabaco, el debate entre la producción y el control de éste continuará. Aunque China ha hecho ya esfuerzos importantes en esta política de control todavía está al principio de su "largo camino" para mejorar el estado de la salud poblacional a partir de la reducción del consumo del tabaco en el país.